Validation of the Lithuanian Version of Moral Competence Test and Application of KMDD in Language Teaching / Learning Process at Vilnius University, Lithuania - Kriaučiūniene Roma; Lind, Georg (ETHICS IN PROGRESS, 2021)
The findings obtained by G. Lind using his original research instrument – the Moral Competence Test – suggest that universities lack the capacity to foster students’ moral competence development. The MCT has been translated into 39 languages, all of which have gone through the necessary validation procedure. The article reports on the MCT validation study for the 40th language, namely Lithuanian. The research sample consisted of 526 students of English/German/French languages, future foreign language teachers, in the 1 st to 4th years of study at two universities in Lithuania: the former Vilnius Pedagogical University and the Vilnius University. The majority of the respondents demonstrated low or medium level of moral competence. On the basis of this cross-sectional study (2019–2020), the MCT for Lithuanian has been successfully validated and certified. In the following article, we present and discuss all the validation criteria and revisit the theoretical background of MCT. We also argue for educating students in moral competence and evaluating the effects of moral competence promotion in academic contexts.